Signaling for the interferon family of receptors and ligands and clinical implications - Platanias, Leonidas (Henry Stewart Talks, 2011)
Mechanisms of action of interferons, Interferon receptors, Interferon activated signaling pathways, Jak-Stat pathways, Map kinase pathways, Akt/mTOR pathway, Interferons and hematopoiesis, Interferons and bone marrow failure